Effects of Medium Chain Fatty Acid Application in Swine Feed on Porcine Epidemic Diarrhea Virus - A. B. Lerner; R. A. Cochrane; J. T. Gebhardt; S. S. Dritz; C. K. Jones; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; J. Bai; E. Porter; J. Anderson; P. C. Gauger; et al. (Kansas Agricultural Experiment Station Research Reports, 2019)
Medium chain fatty acid (MCFA) application has been identified as a promising strategy to decrease viral pathogen transmission in swine feed. Four experiments were conducted to: 1) determine if MCFAs are effective when applied to feed both prior to and after porcine epidemic diarrhea virus (PEDV) inoculation measured by quantitative reverse transcription polymerase chain reaction (qRT-PCR), 2) evaluate the effects of varying amounts and combinations of MCFA measured by qRT-PCR, and 3) evaluate selected MCFA treatments in a bioassay. In Exp. 1, treatments were arranged in a 2 × 2 + 1 factorial with the main effects of chemical treatment (0.3% Sal CURB [Kemin Industries, Des Moines, IA] or 1% MCFA blend of 1:1:1 C6:C8:C10 [PMI, Arden Hills, MN]) and timing of chemical treatment (pre or post-inoculation with PEDV), plus a positive control (feed inoculated with PEDV and no chemical treatment). Feed was treated with the respective treatment either before or after inoculation at which point it remained at ambient temperature for 24 h and then was analyzed via qRT-PCR. The analyzed values represent cycle threshold (Ct), for which a lower number indicates greater detection of viral nucleic acid. Results demonstrated that all combinations of chemical treatment and timing increased Ct compared to the positive control (P<0.05). Additionally, treatment of feed pre-PEDV inoculation resulted in increased Ct value compared to post- inoculation treatment (P= 0.009) and Sal CURB increased Ct in comparison with 1% MCFA (P<0.0001). In Exp. 2, the chemical treatments were applied pre-inoculation and consisted of:1) positive control, 2) 0.3% Sal CURB, 3) 0.125% C6, 4) 0.25% C6, 5) 0.33% C6,6) 0.125% C8, 7) 0.25% C8, 8) 0.33% C8, 9) 0.125% C10, 10) 0.25% C10, 11) 0.33% C10, 12) 0.125% C5, 13) 0.25% C5, 14) 0.33% C5, and 15) 0.66% C5, which were analyzed via qRT-PCR. Treatment of feed with 0.33% C8 resulted in increased (P<0.05) Ct values compared to all other levels of MCFA and the positive control feed. Further, Sal CURB, 0.25% C6, 0.33% C6, all levels of C8, 0.25% C10, 0.33% C10, or 0.66% C5 all had increased Ct values compared to positive control feed (P<0.05). Increasing amounts of each individual MCFA resulted in increased Ct (P<0.045). In Exp. 3, the chemical treatments were applied pre-inoculation and consisted of: 1) positive control; 2) 0.3% Sal CURB; 3) 0.25% MCFA blend; 4) 0.375% MCFA blend; 5) 0.500% MCFA blend; 6) 0.750% MCFA blend; 7) 1.0% MCFA blend; 8) 0.125% C6 + 0.125% C8; 9) 0.25% C6 + 0.25% C8; 10) 0.33% C6 + 0.33% C8; 11) 0.125% C6 + 0.125% C10; 12) 0.25% C6 + 0.25% C10; 13) 0.33% C6 + 0.33% C10; 14) 0.125% C8 + 0.125% C10; 15) 0.25% C8 + 0.25% C10; and 16) 0.33% C8 + 0.33% C10, which were analyzed via qRT-PCR. Treating feed with Sal CURB, 0.500% blend, 0.750% blend, 1.0% blend, all levels of the C6 + C8, 0.25% C6 + 0.25% C10, 0.33% C6 + 0.33% C10, 0.25% C8 + 0.25% C10, or 0.33% C8 + 0.33% C10 resulted in increased Ct compared to the positive control (P<0.05). Lastly, in Exp. 4, feed was treated pre-inoculation with either 1) no treatment (positive control); 2) 0.3% Sal CURB; 3) 0.5% MCFA blend; or 4) 0.3% C8 and samples were analyzed via qRT-PCR and bioassay. Adding either 0.5% MCFA blend or 0.3% C8 resulted in increased Ct compared to the positive control. Further, only the positive control resulted in a positive in vivo bioassay. This set of experiments demonstrates that MCFA and Sal CURB are effective at decreasing detection of PEDV in feed both prior to and post-inoculation. Additionally, inclusion of lower levels of MCFA than previously evaluated may provide protection against PEDV transmission through feed.
Keywords: medium chain fatty acids; PEDV; feed; swine